Perspectivas para el cultivo de ostras en el golfo de Nicoya (ING) - Arias, Sidey (1998)
Studies by the Laboratory of Marine Cultures of the National University on diets, cultchless seed production and evaluation of methods for outdoor growing of oysters (Crassostrea rhizophorae and C. gigas) have been directed toward the development of the oyster culture as an alternative for the fishermen of the Nicoya Gulf, Puntarenas, Costa Rica. Of five diets tested, the mixture of Isochrysis galbana: Chaetoceros gracilis gave the best result with 36% of setting. For the production of cultchless seed two techniques were tested, one preventing setting through induction of metamorphosis with Gaba, L-Dopa, norepinephine and epinephrine, and the second allowing the setting process using grounded oyster shell (250-350μm and 350-425μm ) as substratum. The first method did not give positive results, while the second was relatively successful with 26% and 14% settlement of the larvae for each particulate size. The best results concerning outdoor growing were obtained with C. gigas in 1991 at the inlet of a shrimp farm situated at the Central Pacific Coast, with 78 mm in 7.3 months and 55% survival. The best results with Crassostrea rhizophorae were achieved in shrimp ponds of a farm in the Nicoya Gulf, with a growth of 53 mm in 8 months and a survival rate of 6% (in 1995). Due to severe infestation by Polydora spp., the mortality in the Nicoya Gulf always exceeded 94%. The knowledge so far acquired is being transferred to the fishermen communities of Paquera, Jicaral, and the Isle of Venado, all of them in the Nicoya Gulf.